Revealing a ribbon-like jet in OJ 287 with RadioAstron - Traianou, Efthalia; Gómez, J. L.; Cho, I.; Chael, A.; Fuentes, A.; Myserlis, I.; Wielgus, M.; Zhao, G.-Y.; Lico, R.; Moriyama, K.; Dey, L.; Bruni, G.; et al. (Astronomy and astrophysics, 2025)
We present space-based very long baseline interferometry observations of the BL Lac type object OJ 287 taken with RadioAstron at 22 GHz on April 25, 2016, in conjunction with a ground array comprising 27 radio telescopes. We detect ground-space fringes at projected baselines extending up to 4.6 Earth diameters, which allowed us to image the jet in OJ 287 with an angular resolution of ∼47 μas. Applying an advanced regularized maximum likelihood imaging method, we resolved the innermost jet structure with a complex morphology at a resolution of ∼15 μas (∼0.1 pc projected distance). For the first time, due to a favorable geometrical position of the jet in tandem with high data quality, we detect multiple sharp bends that form a “ribbon-like” jet structure that extends down to 1 mas. Two-dimensional Gaussian model-fitting reveals regions of the jet with brightness temperatures of more than 10 13 K, indicative of strong Doppler boosting. Polarimetric imaging reveals that the electric vector position angles are predominantly perpendicular to the innermost jet direction, implying a dominant poloidal magnetic field component near the central engine. Complementary multi-epoch Very Long Baseline Array observations at 43 GHz provide a multifrequency view of the jet evolution. Ridgeline analysis of the 43 GHz data shows significant variations in the jet position angle from 2014 to 2017, behavior consistent with a rotating helical jet structure. Finally, we confirm the emergence of a new jet component (B15 or K), which may be associated with the source’s first TeV flare, and offer new observational constraints relevant to models involving a supermassive black hole binary.
Gesehen am 18.11.2025